2014
DOI: 10.1111/1744-9987.12210
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Granulocyte and Monocyte Adsorption Apheresis for Treatment of Palmoplantar Pustulosis

Abstract: Palmoplantar pustulosis (PPP) is characterized by neutrophilic pustules with erythema, which are limited to the hands and feet. Although granulocyte and monocyte adsorption apheresis (GMA) has shown remarkable effects on generalized pustular psoriasis, there are few reports of PPP treated with GMA. We treated three refractory PPP patients using GMA weekly for 5 weeks. The skin eruptions were assessed by a 5-grade score for scales, pustules, and erythema. GMA decreased the total grade from 9 to 2 in patients 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Fujisawa et al reported the efficacy of granulocyte and monocyte adsorption apheresis (GMA) to treat PPP. 15) GMA selectively adsorbs Mac-1-expressing neutrophils and reduces serum levels of proinflammatory cytokines. 15) Although inflammatory cytokines are increased after CPB, 16) there has been no report that an extracorporeal membrane oxygenator removes cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Fujisawa et al reported the efficacy of granulocyte and monocyte adsorption apheresis (GMA) to treat PPP. 15) GMA selectively adsorbs Mac-1-expressing neutrophils and reduces serum levels of proinflammatory cytokines. 15) Although inflammatory cytokines are increased after CPB, 16) there has been no report that an extracorporeal membrane oxygenator removes cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In PPPP, various modalities have shown success, including anti‐IL‐6 agent tocilizumab, and anti‐IL‐12 and IL‐23 agent, ustekinumab . GMA may also be effective …”
Section: Treatmentmentioning
confidence: 99%
“…In a previous report, 14 patients with localized pustular psoriasis were treated with GMA resulting in two cases with excellent outcomes, seven effective, three relatively effective and two unresponsive . One report demonstrated the efficacy of GMA against PPP skin manifestations in three patients . There is another report on successful treatment against PPP with extra‐palmoplantar lesions and PAO by GMA .…”
Section: Discussionmentioning
confidence: 99%
“…9 One report demonstrated the efficacy of GMA against PPP skin manifestations in three patients. 10 There is another report on successful treatment against PPP with extra-palmoplantar lesions and PAO by GMA. 11 In our study, an improvement of 50% in the PPPASI score was achieved only by one or two patients of the five after GMA, and deterioration was noted in two patients.…”
Section: Discussionmentioning
confidence: 99%